Wireless bioresorbable electronic system enables sustained nonpharmacological neuroregenerative therapy. (December 2018) - Koo, Jahyun; MacEwan, Matthew; Kang, Seung-Kyun; Won, Sang; Stephen, Manu; Gamble, Paul; Xie, Zhaoqian; Yan, Ying; Chen, Yu-Yu; Shin, Jiho; Birenbaum, Nathan; Chung, Sangjin; et al.
Abstract Peripheral nerve injuries represent a significant problem in public health, constituting 2–5% of all trauma cases1 . For severe nerve injuries, even advanced forms of clinical intervention often lead to incomplete and unsatisfactory motor and/or sensory function2 . Numerous studies report the potential of pharmacological approaches (for example, growth factors, immunosuppressants) to accelerate and enhance nerve regeneration in rodent models3–10 . Unfortunately, few have had a positive impact in clinical practice. Direct intraoperative electrical stimulation of injured nerve tissue proximal to the site of repair has been demonstrated to enhance and accelerate functional recovery11, 12, suggesting a novel nonpharmacological, bioelectric form of therapy that could complement existing surgical approaches. A significant limitation of this technique is that existing protocols are constrained to intraoperative use and limited therapeutic benefits13 . Herein we introduce (i) a platform for wireless, programmable electrical peripheral nerve stimulation, built with a collection of circuit elements and substrates that are entirely bioresorbable and biocompatible, and (ii) the first reported demonstration of enhanced neuroregeneration and functional recovery in rodent models as a result of multiple episodes of electrical stimulation of injured nervous tissue. A biocompatible device built from naturally dissolving components and controlled by wireless technology enables programmable electrical stimulation of injured rodent peripheral nerves to accelerate regeneration and recovery.